PENGARUH MANFAAT, KEPERCAYAAN, EFIKASI DIRI, KEMUDAHAN PENGGUNAAN, KEAMANAN TERHADAP PERSEPSI KONSUMEN PADA MY PERTAMINA (STUDI PADA PENGGUNAAN MY PERTAMINA KOTA BANDUNG) - Rizky Muhammad Ibrahim; Nadya Novandriani Karina Moeliono (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to determine how the Benefits, Trust, Self-Efficacy, Ease of Use, Safety and its influence on consumer perceptions at My Pertamia in the city of Bandung. This type of research is descriptive-causality and quantitative and this study uses secondary and primary data. The sample in this study is the My Pertamina users who are domiciled in the city of Bandung as many as 100 respondents by means of an online google form questionnaire. The sampling technique used is non-probability sampling which includes purposive sampling. This research uses Descriptive Analysis and Multiple Linear Regression Analysis. Based on the simultaneous test results (f test), it can be concluded that the variables of Benefit (X1), Trust (X2), Self-Efficacy (X3), Ease of Use (X4), and Safety (X5) have a significant effect on consumer perceptions of My Pertamina. Furthermore, looking at the results of the partial test (t test), the ease of use variable does not significantly influence consumer perceptions of My Pertamina. Based on the coefficient of determination it is found that the effect of all variables is 80.2%